Comprehensive insights into sustainable circular liquid hydrogen carriers: Analysis of technologies and their role in energy transition - Riham Surkatti (19450312) (2025)
Hydrogen, as a versatile energy carrier, has gained significant attention in recent years due to its potential to address energy and environmental challenges. It is a clean and abundant resource that can be produced through various methods, including electrolysis and reforming processes. However, the widespread use of hydrogen as an energy source is hindered by its storage and transportation limitations. To overcome these challenges, circular liquid hydrogen carriers have emerged as promising solutions. Circular liquid hydrogen carriers refer to chemical compounds that can store and transport hydrogen efficiently. This review provides a comprehensive overview of different types of hydrogen, with a specific emphasis on blue and green hydrogen. It discusses the hydrogen carrier pathway and different hydrogen carrier types, including liquid hydrogen carriers. Additionally, the review highlights common and sustainable liquid hydrogen carriers such as methanol, dimethyl ether, formic acid, and ammonia, exploring their potential, characteristics, and decomposition into hydrogen. Furthermore, it compares the transportation and storage aspects of these hydrogen carriers, considering their economic value and environmental impact. It also delves into the advantages and disadvantages of hydrogen carriers and production techniques, while proposing challenging areas for future research. Among several sustainable hydrogen carriers, DME, with its lower energy density, could be suitable for specific applications where its unique properties are advantageous. Qatar’s advanced LNG infrastructure supports the adaptation of existing supply chains for hydrogen export, including LOHC and ammonia. These efforts strengthen Qatar’s position in the global hydrogen economy, with further advancements needed for large-scale implementation. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2025.118197